L’uomo esiste nella verità - Venturelli, Domenico (Bollettino Filosofico, 2016)
In human awareness of the mystery of all life, with reference to the thoughts of Nietzsche, Heidegger and Jaspers, the author develops in this paper a personal perspective, which gravitates around the concept of truth understood in his original sense: not the truth depending by assumptions and scientific research’s methods which, by appearances, exists even without us, but the truth concerning the full meaning of birth and death, which can not exist without the witness of the one who makes it live, here and now, in the time, in the incarnated form, in communication with others. This is the truth as source which transcends us and yet claims for us, appealing - in order to exist - to our freedom: only in her breath exists the human being.